Practical Considerations for the Daratumumab Management in Portuguese Routine Clinical Practice: Recommendations From an Expert Panel of Hematologists - Geraldes, Catarina; Neves, Manuel; Chacim, Sérgio; da Costa, Fernando Leal (Frontiers in Oncology, 2022)
The recent therapeutic progress in multiple myeloma (MM) has led to the introduction of novel and highly potent drug classes. Daratumumab was the first CD38-targeting antibody showing to be effective and safe in MM patients as monotherapy and in combination regimens, which led to its rapid implementation in clinical practice. Considering that treatment discontinuation for drug-related adverse events can impact patients’ quality of life and outcomes, the treatment decision should consider different factors and be weighted for each patient individually. Here, we aimed to guide clinicians using daratumumab treatment for MM by addressing practical real-world considerations based on an expert panel of Portuguese hematologists. Carefully following the recommendations mentioned in daratumumab’s SmPC, and of those from other drugs used in combination regimens, along with ensuring a good communication with all healthcare professionals involved, is critical to prevent any complications arising from treatment. The risk of infection should be assessed for all patients under treatment with daratumumab and patients should be educated on the potential adverse events. Recommendations on prophylaxis and vaccination should be considered to avoid infections, and delays in the planned therapeutic schedule may be required to prevent adverse consequences of hematological toxicity. Daratumumab treatment is effective and feasible in patients with renal impairment, although careful patient monitoring and a frequent communication with the Nephrology department are of the utmost importance. Sharing clinical practice plays an important role in medical education by allowing to maximize treatment efficacy and minimize its safety risks.